From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.